What factors affecting firm value during IPOs? A study at the Indonesia Stock Exchange - Abdul Latif; Indra Permana; Zulfa Zakiatul Hidayah (Journal of Enterprise and Development (JED), 2023)
Purpose — The objective of this study is to examine the factors that impact the value of a company over both the short and long term. These factors include variables such as the company's size, the reputation of the underwriter and auditor, the industry sector in which it operates, and the number of shares outstanding during the initial public offering (IPO).Method — In this study, a quantitative causality approach with analytical properties is employed as the method of analysis. The population under investigation consists of companies that conducted initial public offerings (IPOs) between the years 2020 and 2022. A sample size of 113 companies is selected using a specific sampling approach for research purposes. To analyze the data, a binary logistic regression model is applied, along with the use of statistical tools.Result — The conducted research has yielded several findings. Firstly, it indicates that the variable of company size does not have a significant impact. Secondly, the variable of underwriter reputation also does not have a significant effect. Thirdly, the variable of auditor reputation does not significantly influence firm value. Fourthly, the stock variable does not significantly affect firm value. Lastly, the research highlights that the industry sector variable has a significant impact on firm value.Contribution — The research is expected to contribute to the academic field and benefit capital market players by addressing the factors that should be considered when making investment decisions in the capital market.